Protocol for a pilot randomised controlled trial evaluating feasibility and acceptability of cognitive remediation group therapy compared with mutual aid group therapy for people ageing with HIV-associated neurocognitive disorder (HAND) in Toronto, Canada - Andrew David Eaton; Shelley L Craig; John W McCullagh; Sharon L Walmsley; Sean B Rourke; Teresa Sota; Barbara A Fallon (BMJ Open)
Introduction HIV-associated neurocognitive disorder (HAND) may affect 30%–50% of people ageing with HIV. HAND may increase stress and anxiety, and impede coping. Psychosocial group therapy may ameliorate HAND’s symptoms, yet the ideal intervention is unclear. This protocol outlines a pilot randomised controlled trial (RCT)—designed using community-based participatory research—to pilot cognitive remediation group therapy (CRGT) against an active comparator.Methods and analysis This is a pilot, parallel design, two-arm RCT that will recruit participants diagnosed with the mild neurocognitive disorder form of HAND from a neurobehavioural research unit at a tertiary care hospital in Toronto, Canada. Eligibility criteria include age ≥40 years, known HIV status for 5+ years, English fluency, able to consent and able to attend 8 weeks of group therapy. Eligible participants will be randomised to one of two treatment arms, each consisting of eight-session group interventions delivered once weekly at 3 hours per session. Arm 1 (novel) is CRGT, combining mindfulness-based stress reduction with brain training activities. Arm 2 (active control) is mutual aid group therapy. The primary outcomes are feasibility, measured by proportions of recruitment and completion, and acceptability, determined by a satisfaction questionnaire. The secondary outcome is intervention fidelity, where content analysis will be used to assess facilitator session reports. A between-group analysis will be conducted on exploratory outcomes of stress, anxiety, coping and use of intervention activities that will be collected at three time points.Ethics and dissemination Ethical approval was obtained from the Research Ethics Boards of St. Michael’s Hospital and the University of Toronto. Findings will be disseminated through peer-reviewed publications, conference presentations and community reporting. This study could provide insight into design (eg, recruitment, measures) and intervention considerations (eg, structure, content) for a larger trial to lessen the burden of cognitive decline among people ageing with HIV.Trial registration number NCT03483740; Pre-results